Coping Mechanisms among High School Students in Bangkok - Sawasdisutha, Prathana; Hongsanguansri, Sirichai (Journal of the Psychiatric Association of Thailand, 2016)
Objective : To study the coping styles among high school students in Bangkok and the relationship between coping mechanisms and depression. Methods : A cross-sectional survey was conducted in high school students in Bangkok. The participants were selected by stratified random sampling. The Adolescent Coping Scale in Thai version and The Center for Epidemiologic Studies-Depression Scale in Thai version were used. The association between coping mechanisms and depression was analyzed by Independent t-test, Chi-square and ANOVA. Results : The participants were 700 students ; 280 males (40%), 420 females (60%), mean age of 16.5 ± 1.3 years. 114 males (42.4%) and 170 females (41.4%) had depression. The coping mechanisms among high school students were predominately in “seek relaxing diversions” (82.3%), “investing in close friend” (70.3%) and “work and achieve” (68.4%). Males and females used coping mechanism differently. Females used the problem-focus coping style more frequent than males. Style of coping mechanisms associated with depression found that depressed students frequently used more “non-productive coping” than healthy students as follows : wishful thinking (64.1 vs 58.2, p < .001), keep to self (67.2 vs 56.0, p < .001), self blame (58.9 vs 45.5, p < .001), worry (58.8 vs 46.0, p < .001), ignore the problem (53.4 vs 45.7, p < .001), not cope (43.3 vs 34.6, p < .001) and tension reduction (51.4 vs 40.0, p < .001). Conclusion : Some high school students still use coping strategies unsuitably when react to stress ,especially in male students and depressed students. There is a statistically significant correlations between “non-productive coping” and “depression”. Accordingly, the coaching program for practicing “coping skills” is necessary among Thai high school students.